2009
DOI: 10.17221/1658-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Effects in genetic evaluation for semen traits in Czech Large White and Czech Landrace boars

Abstract: Artificial insemination (AI) has become an important procedure in the global pig industry. Compared with natural service, artificial insemination allows the greater use of genetically superior sires (Oh et al., 2006). Selection practices for AI boars are universally based on the genetic evaluations for economically important traits (Robinson and Buhr, 2005). For example, boars of dam breeds kept in the Czech Republic are mainly selected for average daily gain from birth till the end of the performance test, le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 22 publications
4
17
0
Order By: Relevance
“…The results of the present study were consistent with the research of Szostak & Sarzyńska (2011), who found statistically significant differences between breeds in the average expression and variability of libido. There was a tendency towards increase in ejaculate volume with age of boar, which was similar to the results presented by Jankevičiûtė & Žilinskas (2002), Wolf & Smital (2009a;b), Banaszewska & Kondracki (2012) and Savić et al (2013). In the research of Frangež et al (2005), the best libido was manifested when the ejaculate was collected twice a week, whereas shortening the interval between two collections resulted in a decline in libido.…”
Section: Resultssupporting
confidence: 88%
“…The results of the present study were consistent with the research of Szostak & Sarzyńska (2011), who found statistically significant differences between breeds in the average expression and variability of libido. There was a tendency towards increase in ejaculate volume with age of boar, which was similar to the results presented by Jankevičiûtė & Žilinskas (2002), Wolf & Smital (2009a;b), Banaszewska & Kondracki (2012) and Savić et al (2013). In the research of Frangež et al (2005), the best libido was manifested when the ejaculate was collected twice a week, whereas shortening the interval between two collections resulted in a decline in libido.…”
Section: Resultssupporting
confidence: 88%
“…The effect of daylight within photoperiod interval is in agreement with the research of Knecht et al (2013), in which a significant effect of photoperiod was determined on the variability of ejaculate volume. There is a trend of increase in the volume of ejaculate with the increase in boar age, which is consistent with the investigations of Wolf and Smital (2009), Banaszewska and Kondracki (2012), and Savić et al (2013). The increase in ejaculate volume with aging also agrees with the results of Kondracki et al (2013), who showed that in boar, the volume increased at the beginning of utilisation, after three months and after six months of exploitation (221.72, 251.14, and 269.20 mL).…”
Section: Discussionsupporting
confidence: 91%
“…It could be caused by variation of temperature in the summer season. Several studies have shown that elevated ambient temperatures, heat stress and/or hot weather have an adverse effect on sperm production (McNitt et al, 1970;Colenbrander et al, 1993;Frydrychová et al, 2007;Wolf et al, 2009) and sperm morphology in boars (Larsson et al, 1984;Malmgren, 1989). On the other hand, it could also be an influence of the hereditary background (Čeřovský, 2005).…”
Section: Discussionmentioning
confidence: 99%